(untitled) (Comparative & International Education Series, 2021)
Chapter 6|15 pages International Students’ Career Development Preparation at the American Community College By Hannah Rapp, Yi-jung Wu, Ran Liu, Xiaoli Jing With the accelerating trends of globalization, neoliberalism, and education internationalization, an increasing number of international students choose to study in U.S. community colleges. In order to understand these students’ unique career development path, our chapter reviews the career expectations and aspirations of international students attending U.S. community colleges, the common challenges during their career preparations, and the effectiveness of on-campus career services provided by community colleges. We then discuss the limitations of the current research and provide future research directions. In the end, we present implications of the findings for community colleges to better support international students’ career development needs.